Grill and Toast Restaurant/ Muhammad Imran Sabri - Muhammad Imran, Sabri (2020)
Grill and Toast Restaurant will be moderately priced 60 seat restaurant offering traditional food and self-service. Emping, Ayam Buah Keluak, Opok-Opok, Kerabu Sare and any other things are all on the menu. The restaurant will be own by sole proprietorship and under experienced management, headed by General, Muhammad Imran bin Sabri. The restaurant will have a Finance Manager, an Operations Manager, a Marketing Manager and Administrative Manager this organization emphasizes functional specialities to perform task. Grill and Toast Restaurant will be located at Jeti Semeling, 08000, Sg. Petani, Kedah. Although the location was previously utilized as a restaurant, the former tenant removed the majority of the furniture, fixtures, and equipment which will need to be replaced. The location will also require some additional renovation to increase table space in dining area. The restaurant will operate five days a week. Sales projection assume 300 customers per month and RM15.00 per person resulting in month’s sales of just over RM25,000.00 or RM363,000.00 annually. Our pricing strategy will be based on the objectives to get reasonable profit and ensure the satisfaction of the customers to continue doing the business in the future.